Strategies Addressing Barriers to the Implementation of a Pediatric Hand Fracture Care Pathway. Issue 3 (28th March 2023) - Baykan, Altay; Lafreniere, Ann-Sophie; Fraulin, Frankie O.G.; Hartley, Rebecca; Harrop, Alan Robertson; Love, Shannan; Ronksley, Paul; Donald, Maoliosa
Abstract : Background: We recently highlighted shortcomings in the care of pediatric hand fractures in our local context. The Calgary Kids' Hand Rule (CKHR) was developed to predict hand fractures that require referral to a hand surgeon. The aims of this study were to identify barriers to a new care pathway for pediatric hand fractures, based on the CKHR and to generate tailored strategies to support its implementation. Methods: We performed a conventional content analysis of transcripts from four focus groups (parents, emergency/urgent care physicians, plastic surgeons, and hand therapists) to identify relevant concepts (facilitators and barriers). These concepts were mapped to two frameworks. Generic strategies to address the barriers were identified, and further discussions with key stakeholders resulted in tailored strategies for implementation. Results: Five facilitators to implementation of a CKHR-based hand fracture care pathway included established rapport between hand therapists and surgeons, potential for more streamlined care, agreement on identifying another care provider, positive perceptions of hand therapist expertise, and opportunity for patient education. Two individual barriers were concern for poor outcomes and trust. Three systemic barriers were awareness and usability, referral process, and cost and resources. Strategies to address these barriers include pilot-testing of the new care pathway, ensuring closed loop communication, multiple knowledge translation activities, integration of CKHR into the clinical information system, coordinating care and development of parent handouts. Conclusion: Mapping barriers to established implementation frameworks has informed tailored implementation strategies, bringing us one step closer to successfully implementing a new pediatric hand fracture pathway.